Consequential Responsibility for Client Wrongs: Lehman Brothers and the Regulation of the Legal Profession. Issue 1 (2nd January 2013) - Kershaw, David; Moorhead, Richard
<x xml:space="preserve">Abstract</x> Should transactional lawyers bear responsibility when their competent actions facilitate unlawful activity by their client? Or is a lawyer's only concern to act in the client's interest by providing her with the advice and support she seeks? The high profile failure of Lehman Brothers provides a unique opportunity to explore these questions in the context of the provision of a legal opinion by a magic circle law firm. A legal opinion which, although as a matter of law was accurate, was a necessary precursor to an accounting treatment by Lehman Brothers which was described by the Lehman's Bankruptcy Examiner as 'balance sheet manipulation'. The article argues that the law's existing understanding of when consequential responsibility should be imposed on those who assist another's wrongdoing provides a theory and a tool‐kit whose application can be justifiably extended to the professional regulation of transactional lawyers.